2013
DOI: 10.1182/blood-2013-01-476333
|View full text |Cite
|
Sign up to set email alerts
|

CXCL13 plus interleukin 10 is highly specific for the diagnosis of CNS lymphoma

Abstract: Key Points• CXCL13 and CXCL12 mediate chemotaxis of CNS lymphoma cells, and CXCL13 concentration in CSF is prognostic.• CXCL13 plus IL-10 is highly specific for the diagnosis of CNS lymphoma.Establishing the diagnosis of focal brain lesions in patients with unexplained neurologic symptoms represents a challenge. The goal of this study is to provide evidence supporting functional roles for CXC chemokine ligand (CXCL)13 and interleukin (IL)-10 in central nervous system (CNS) lymphomas and to evaluate the utility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
176
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(189 citation statements)
references
References 37 publications
(52 reference statements)
10
176
1
2
Order By: Relevance
“…Our group detected elevated CXCL13 concentration in CSF of 30 PCNSL patients as compared to patients with other CNS malignancies and non-malignant CNS diseases [13]. These findings were confirmed in an analysis of 60 PCNSL and 23 SCNSL samples [14]. Viaccoz et al identified neopterin, a nonspecific marker of CNS inflammation, as possible marker to differentiate PCNSL from other brain tumours [15].…”
Section: Introductionsupporting
confidence: 72%
“…Our group detected elevated CXCL13 concentration in CSF of 30 PCNSL patients as compared to patients with other CNS malignancies and non-malignant CNS diseases [13]. These findings were confirmed in an analysis of 60 PCNSL and 23 SCNSL samples [14]. Viaccoz et al identified neopterin, a nonspecific marker of CNS inflammation, as possible marker to differentiate PCNSL from other brain tumours [15].…”
Section: Introductionsupporting
confidence: 72%
“…Peripheral monocytes, which migrate to cancer tissue and differentiate into tumor-associated macrophages, are increased in a variety of malignancies, including lymphoma. 18 The M2c subtype of monocytes can produce CXCL13 and interleukin-10, 19,20 which are known to be associated with the development of CNS lymphoma. 19 Accordingly, AMC at diagnosis in DLBCL patients may be related to CNS relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Particular organ-specific tumor markers such as CA 15-3, CA 125, CA 19-9, CA724, AFP, NSE, Cyfra 21-1, EGFR, a-fetoprotein, b-human chorionic gonadotropin can be relatively specific for LM when elevated in CSF in the absence of markedly elevated serum levels 6,[11][12][13][14] . Nonspecific tumor markers such as molecules involved in CNS penetration (eg, matrix metalloproteinases and cathepsins), tumor cell tropism (eg, chemokines CXCL8 and CCL18) and vascular endothelial growth factor can be strong indirect indicators of LM but none are sensitive enough to improve the cytological diagnosis 3,6,11,17 . CSF antithrombin III levels have been suggested as a useful biomarker in patients with primary CNS lymphoma, but have not been evaluated in patients with lymphomatous meningitis 6,15 .…”
mentioning
confidence: 99%